iFIT - Petrič, Boštjan (Acta chimica slovenica, 2022)
The area where a progress curve exhibitsmaximum curvature contains the most information about kinetic parameters. To determine these parameters more accurately from progress curves, we propose an iterative approach that calculates the area of maximum curvature based on an estimate of kinetic parameters and then recalculates the parameters based on time-concentration data points within this area. Based on this algorithm, we developed a computer script called iFIT as a free web application at http://www.i-fit.si. The benefits of working with iFIT are that it decreases the importance of initial substrate concentration and the impact of certain side reactions on the final calculated kinetic parameters.
Keywords: encimsko-kinetični parametri; enzyme-kinetic parameters; integrated Michaelis-Menten equation; integrirana Michaelis-Mentenova enačba; krivulje napredka; progress curves